Low-carbon magnesia-carbon refractory material for clean steel smelting and preparation method of low-carbon magnesia-carbon refractory material

By introducing additives such as erpentine and mullite into low-carbon magnesium carbon refractory materials, and using phenolic resin and high-temperature pressing molding technology, the problem of poor performance of existing materials at high temperatures is solved, and refractory materials with excellent oxidation resistance, thermal shock resistance and slag resistance are prepared, which is suitable for clean steel smelting.

CN119591412APending Publication Date: 2025-03-11HUNAN INST OF TECH

Patent Information

Application Number
CN202411554021.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-04
Publication Date
2025-03-11

AI Technical Summary

Technical Problem

The existing low-carbon magnesium carbon refractory materials have problems such as thermal shock stability, slag corrosion resistance and oxidation resistance in high-temperature kilns and high-temperature containers, and cannot meet the needs of high-quality clean steel smelting.

Method used

Components including 40-50 wt% electromelted magnesium sand, 20-30 wt% electromelted magnesium sand, 10-20 wt% electromelted magnesium sand, 8-12 wt% silicon powder, 1-3 wt% alumina powder, 3-5 wt% flake graphite, 2-4 wt% composite additives (myrolite and mullite) and 4-6 wt% phenolic resin were prepared by high-temperature press molding, curing and carbon buried heat treatment.

Benefits of technology

It significantly improves the oxidation resistance, thermal shock resistance and slag resistance of low-carbon magnesium carbon refractory materials. It is suitable for clean steel smelting, and has a simple process and low cost.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119591412A_ABST
    Figure CN119591412A_ABST
Patent Text Reader

Abstract

The invention discloses a low-carbon magnesia-carbon refractory material for clean steel smelting and a preparation method thereof, and relates to the technical field of magnesia-carbon refractory materials. The low-carbon magnesia-carbon refractory material comprises the following components: 40-50 wt% of fused magnesite with the particle size of 3-5 mm, 20-30 wt% of fused magnesite with the particle size of 1-3 mm, 10-20 wt% of fused magnesite with the particle size of less than or equal to 74 [mu] m, 8-12 wt% of silicon powder, 1-3 wt% of alumina powder and 3-5 wt% of crystalline flake graphite. 2-4 wt% of a composite additive and 4-6 wt% of phenolic resin are added; the composite additive comprises andalusite and mullite. The material has excellent mechanical properties, thermal shock resistance, oxidation resistance and erosion resistance; the preparation method has the characteristics of low cost and simple process, and the prepared low-carbon magnesia carbon refractory material has excellent oxidation resistance, thermal shock resistance and slag resistance by exerting the phase volume expansion effect and intergranular phase enhancement effect of the multiphase ceramic; the used graphite is low in content, graphite consumption and molten steel recarburization risk can be reduced, and the method is suitable for smelting clean steel.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of magnesium-carbon refractory materials, and in particular to a low-carbon magnesium-carbon refractory material for clean steel smelting and a preparation method thereof. Background Art

[0002] As key structural materials and components for high-temperature kilns and containers, refractory materials are indispensable supporting materials for high-temperature industries such as steel, metallurgy, petrochemicals, and even defense and military industries. Currently, low-carbon magnesium-carbon refractory materials used in industry have outstanding problems of poor thermal shock stability, slag corrosion resistance, and oxidation resistance, and cannot meet the needs of high-quality clean steel smelting. It is urgent to develop high-quality, long-life low-carbon magnesium-carbon refractory materials to support the implementation of new processes and technologies in the high-temperature industrial field.

[0003] In recent years, by introducing additives into carbon-containing refractory materials, ceramic phases with excellent properties such as high thermal conductivity, high fracture toughness, and good oxidation resistance are generated in situ, showing great potential and can effectively solve the bottleneck problem of poor high-temperature service performance of magnesium-carbon refractory materials due to low carbonization.

[0004] Mullite has excellent properties such as high melting point, good mechanical properties and thermal shock resistance. The mullitization of andalusite generates needle-shaped or columnar mullite and a small amount of low-melting phase of silica through high-temperature decomposition, resulting in micro-volume expansion to block pores, hindering the entry of oxygen and the penetration of slag. At the same time, part of the low-melting phase silica is excluded from andalusite and enters cracks and pores, and then is reconstructed by high temperature to transform into a high-melting ceramic phase, which can establish a strong chemical bond between the aggregate and the matrix, improving the thermal shock resistance of the material. Therefore, the introduction of andalusite and mullite composites and their coupling effect can achieve a synergistic improvement in the oxidation resistance, thermal shock resistance and erosion resistance of low-carbon magnesium-carbon refractory materials. However, there has been no report on the application of andalusite and mullite composite powders in low-carbon magnesium-carbon refractory materials. Summary of the invention

[0005] One of the purposes of the present invention is to provide a low-carbon magnesium-carbon refractory material for clean steel smelting with excellent service performance.

[0006] In order to achieve the above-mentioned purpose, the present invention adopts the following technical scheme: a low-carbon magnesium-carbon refractory material for clean steel smelting, comprising the following components: 40-50wt% of fused magnesia with a particle size of 3-5mm, 20-30wt% of fused magnesia with a particle size of 1-3mm, 10-20wt% of fused magnesia with a particle size of ≤74μm, 8-12wt% of silicon powder, 1-3wt% of alumina powder, 3-5wt% of flake graphite; 2-4wt% of composite additives and 4-6wt% of phenolic resin are added; the composite additives include the following components: andalusite and mullite.

[0007] Wherein, the mass ratio of andalusite to mullite is 1:(1-3).

[0008] Wherein, the particle size of the andalusite is ≤38 μm, and the purity is ≥80wt%; the particle size of the mullite is ≤44 μm, and the purity is ≥96wt%.

[0009] Wherein, the purity of the fused magnesia is ≥98wt%.

[0010] Wherein, the particle size of the silicon powder is ≤74 μm and the purity is ≥99wt%.

[0011] Wherein, the particle size of the alumina powder is 5 to 6 μm, and the purity is ≥ 99wt%.

[0012] Wherein, the particle size of the flake graphite is ≤150 μm and the purity is ≥98wt%.

[0013] Wherein, the phenolic resin is a thermosetting phenolic resin with a solid content of ≥73wt%.

[0014] Another object of the present invention is to provide a method for preparing a low-carbon magnesium-carbon refractory material for clean steel smelting, which comprises the following steps: Firstly, magnesia fine powder (fused magnesia with a particle size of ≤74 μm), silicon powder, alumina powder, flake graphite and composite additives are mixed to obtain composite powder; then magnesia aggregate (fused magnesia with a particle size of 3-5 mm and fused magnesia with a particle size of 1-3 mm) is mixed with phenolic resin, and then the composite powder is added and the secondary mixing is uniform; the materials are pressed, solidified and subjected to carbon embedding heat treatment to obtain low-carbon magnesium-carbon refractory materials for clean steel smelting.

[0015] Furthermore, the pressure of the compression molding is 150-200 MPa, the temperature of the curing is 90-120° C., the time is 12-18 hours, and the temperature of the heat treatment is 1400-1500° C., the time is 3-5 hours.

[0016] Compared with the prior art, the present invention has the following beneficial effects: 1. The aluminum oxide and silicon powder used in the present invention generate magnesium aluminum spinel, silicon carbide and forsterite in situ at high temperature. Silicon carbide has a strong affinity for oxygen, which can slow down the oxidation of graphite and improve the material's anti-oxidation performance. Silicon carbide reacts with carbon monoxide gas to generate carbon, which can make up for the loss of carbon source; magnesium aluminum spinel and forsterite can absorb and solid-dissolve elements such as magnesium, aluminum and iron in the slag to generate spinel and high-temperature solid solution, improving the material's anti-corrosion performance.

[0017] 2. The andalusite used in the present invention will decompose at high temperature to generate columnar mullite and a small amount of low-melting silicon dioxide phase, resulting in micro-volume expansion to block pores, hinder the entry of oxygen and the penetration of slag, and improve the material's antioxidant and erosion resistance; the low-melting silicon dioxide phase is excluded from the andalusite and enters cracks and pores, and then is reconstructed at high temperature to be converted into high-melting silicon carbide and forsterite phases, establishing a strong chemical bond between the aggregate and the matrix, and improving the bonding strength between the matrix, thereby significantly improving the mechanical properties and thermomechanical properties of the refractory material.

[0018] 3. The present invention makes use of the volume expansion effect and intergranular phase strengthening effect of in-situ multiphase ceramic phases (such as silicon carbide, forsterite, magnesia-alumina spinel and mullite) to make the prepared low-carbon magnesium-carbon refractory material have excellent oxidation resistance, thermal shock resistance and slag resistance.

[0019] 4. The present invention adopts andalusite powder and mullite powder with micron size, and utilizes the size effect to improve the porosity of the material. Meanwhile, the excellent thermal shock stability and oxidation resistance of mullite improve the high temperature service performance of magnesium-carbon refractory materials.

[0020] 5. The graphite content used in the present invention is low, which can reduce the risk of carbon increase in molten steel. The prepared magnesium-carbon refractory material has excellent thermal shock resistance, oxidation resistance and corrosion resistance, and is suitable for clean steel smelting.

[0021] In summary, the present invention has the characteristics of low cost and simple process. The prepared low-carbon magnesium-carbon refractory material for clean steel smelting has excellent oxidation resistance, thermal shock resistance and slag resistance. The graphite content used is low, which can reduce the consumption of non-renewable resource graphite and the risk of carbon increase in molten steel, and is suitable for the smelting of clean steel. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] Figure 1 This is a SEM picture of the low-carbon magnesium-carbon refractory material for clean steel smelting prepared by the present invention. DETAILED DESCRIPTION

[0023] In order to facilitate the understanding of those skilled in the art, the present invention is further described below in conjunction with the examples, and the contents mentioned in the examples are not limitations of the present invention. It should be noted in advance that the following examples were completed in the laboratory, and those skilled in the art should understand that the amounts of the components given in the examples only represent the ratio relationship between the components, rather than specific limitations.

[0024] The present invention provides a method for preparing a low-carbon magnesium-carbon refractory material for clean steel smelting, which is specifically as follows: The raw materials are 40-50wt% of 3-5mm fused magnesia (indicating a particle size of 3-5mm), 20-30wt% of 1-3mm fused magnesia (indicating a particle size of 1-3mm), 10-20wt% of ≤74μm fused magnesia (indicating a particle size of ≤74μm), 8-12wt% of silicon powder, 1-3wt% of alumina powder, 3-5wt% of flake graphite, and 2-4wt% of composite additives and 4-6wt% of phenolic resin. First, magnesia fine powder, silicon powder, alumina powder, flake graphite and composite additives are mixed to obtain composite powder; then, magnesia aggregate is mixed with phenolic resin, and then the composite powder is added to make the secondary mixing uniform; the pressing is carried out at 150-200MPa, and the pressing is carried out at 90-120°C for 12-18h; then, the pressed body is buried in coke, kept warm at 1400-1500°C for 3-5h, and cooled naturally to obtain low-carbon magnesium-carbon refractory material for clean steel smelting.

[0025] The composite additive comprises andalusite and mullite, and the mass ratio of andalusite to mullite is 1:(1-3).

[0026] Among them, the particle size of andalusite is ≤38μm, and the purity is ≥80wt%; the particle size of mullite is ≤44μm, and the purity is ≥96wt%.

[0027] Among them, the purity of fused magnesia is ≥98wt%.

[0028] Among them, the particle size of silicon powder is ≤74μm and the purity is ≥99wt%.

[0029] The particle size of the alumina powder is 5 to 6 μm, and the purity is ≥ 99 wt%.

[0030] Among them, the particle size of flake graphite is ≤150μm and the purity is ≥98wt%.

[0031] Wherein, the phenolic resin is a thermosetting phenolic resin, and the solid content is ≥73wt%.

[0032] Among them, the magnesia fine powder is fused magnesia with a particle size of ≤74μm (referred to as "≤74μm fused magnesia"), and the magnesia aggregate is fused magnesia with a particle size of 3-5mm (referred to as "3-5mm fused magnesia") and fused magnesia with a particle size of 1-3mm (referred to as "1-3mm fused magnesia").

[0033] The following is a detailed description with specific examples. Example 1

[0034] In this embodiment, low-carbon magnesium-carbon refractory materials for clean steel smelting are prepared according to the following method: 40wt% 3-5mm fused magnesia, 25wt% 1-3mm fused magnesia, 19wt% ≤74μm fused magnesia, 8wt% silicon powder, 3wt% alumina powder, 5wt% flake graphite are used as raw materials, and 4wt% composite additives (andalusite, mullite) and 5wt% phenolic resin are added. First, magnesia fine powder, silicon powder, alumina powder, flake graphite and composite additives are mixed to obtain composite powder; then magnesia aggregate is mixed with phenolic resin, and then the above composite powder is added, and the secondary mixing is uniform; it is pressed under 200MPa and cured at 110℃ for 12h; then the pressed body is buried in coke, kept at 1500℃ for 4h, and cooled naturally to obtain low-carbon magnesium-carbon refractory materials for clean steel smelting, such as Figure 1 .

[0035] The mass ratio of andalusite to mullite in the composite additive is 1:1.

[0036] After inspection and testing, the properties of the low-carbon magnesium-carbon refractory material for clean steel smelting prepared in this embodiment are as follows: the room temperature compressive strength is 61MPa, the high temperature flexural strength is 12MPa (1400℃ insulation for 30min); the thermal shock stability can reach 52 times without cracking (1100℃ insulation for 30min, air cooling method); the oxidation index is 19% (1500℃ oxidation for 3h); the erosion index is 35% (1500℃ erosion for 3h). Example 2

[0037] In this embodiment, low-carbon magnesium-carbon refractory materials for clean steel smelting are prepared according to the following method: 45wt% 3-5mm fused magnesia, 28wt% 1-3mm fused magnesia, 11wt% ≤74μm fused magnesia, 10wt% silicon powder, 2wt% alumina powder, 4wt% flake graphite are used as raw materials, and 2wt% composite additives (andalusite, mullite) and 4wt% phenolic resin are added. First, magnesia fine powder, silicon powder, alumina powder, flake graphite and composite additives are mixed to obtain composite powder; then magnesia aggregate is mixed with phenolic resin, and then the above composite powder is added, and the secondary mixing is uniform; it is pressed and formed under 150MPa and cured at 120℃ for 12h; then the pressed body is buried in coke, kept at 1400℃ for 5h, and cooled naturally to obtain low-carbon magnesium-carbon refractory for clean steel smelting.

[0038] The mass ratio of andalusite to mullite in the composite additive is 1:3.

[0039] After inspection and testing, the properties of the low-carbon magnesium-carbon refractory material for clean steel smelting prepared in this embodiment are as follows: the room temperature compressive strength is 52MPa, the high temperature flexural strength is 11MPa (1400℃ insulation for 30min); the thermal shock stability can reach 60 times without cracking (1100℃ insulation for 30min, air cooling method); the oxidation index is 18% (1500℃ oxidation for 3h); the erosion index is 40% (1500℃ erosion for 3h). Example 3

[0040] In this embodiment, low-carbon magnesium-carbon refractory materials for clean steel smelting are prepared according to the following method: 50wt% 3-5mm fused magnesia, 20wt% 1-3mm fused magnesia, 10wt% ≤74μm fused magnesia, 12wt% silicon powder, 3wt% alumina powder, 5wt% flake graphite are used as raw materials, and 3wt% composite additives (andalusite, mullite) and 6wt% phenolic resin are added. First, magnesia fine powder, silicon powder, alumina powder, flake graphite and composite additives are mixed to obtain composite powder; then magnesia aggregate is mixed with phenolic resin, and then the above composite powder is added, and the secondary mixing is uniform; it is pressed and formed under 180MPa and cured at 90℃ for 18h; then the pressed body is buried in coke, kept warm at 1450℃ for 3h, and cooled naturally to obtain low-carbon magnesium-carbon refractory for clean steel smelting.

[0041] The mass ratio of andalusite to mullite in the composite additive is 1:2.

[0042] After inspection and testing, the properties of the low-carbon magnesium-carbon refractory material for clean steel smelting prepared in this embodiment are as follows: the room temperature compressive strength is 57MPa, the high temperature flexural strength is 14MPa (1400℃ insulation for 30min); the thermal shock stability can reach 56 times without cracking (1100℃ insulation for 30min, air cooling method); the oxidation index is 17% (1500℃ oxidation for 3h); the erosion index is 36% (1500℃ erosion for 3h). Example 4

[0043] In this embodiment, low-carbon magnesium-carbon refractory materials for clean steel smelting are prepared according to the following method: 40wt% 3-5mm fused magnesia, 30wt% 1-3mm fused magnesia, 15wt% ≤74μm fused magnesia, 11wt% silicon powder, 1wt% alumina powder, 3wt% flake graphite are used as raw materials, and 4wt% composite additives (andalusite, mullite) and 4wt% phenolic resin are added. First, magnesia fine powder, silicon powder, alumina powder, flake graphite and composite additives are mixed to obtain composite powder; then magnesia aggregate is mixed with phenolic resin, and then the above composite powder is added, and the secondary mixing is uniform; it is pressed and formed under 160MPa and cured at 100℃ for 16h; then the pressed body is buried in coke, kept at 1400℃ for 5h, and cooled naturally to obtain low-carbon magnesium-carbon refractory for clean steel smelting.

[0044] The mass ratio of andalusite to mullite in the composite additive is 1:3.

[0045] After inspection and testing, the properties of the low-carbon magnesium-carbon refractory material for clean steel smelting prepared in this embodiment are as follows: the room temperature compressive strength is 63MPa, the high temperature flexural strength is 14MPa (1400℃ insulation for 30min); the thermal shock stability can reach 45 times without cracking (1100℃ insulation for 30min, air cooling method); the oxidation index is 20% (1500℃ oxidation for 3h); the erosion index is 41% (1500℃ erosion for 3h). Example 5

[0046] In this embodiment, low-carbon magnesium-carbon refractory materials for clean steel smelting are prepared according to the following method: 44wt% 3-5mm fused magnesia, 22wt% 1-3mm fused magnesia, 20wt% ≤74μm fused magnesia, 9wt% silicon powder, 2wt% alumina powder, 3wt% flake graphite are used as raw materials, and 3wt% composite additives (andalusite, mullite) and 5wt% phenolic resin are added. First, magnesia fine powder, silicon powder, alumina powder, flake graphite and composite additives are mixed to obtain composite powder; then magnesia aggregate is mixed with phenolic resin, and then the above composite powder is added, and the secondary mixing is uniform; it is pressed under 200MPa and cured at 120℃ for 12h; then the pressed body is buried in coke, kept warm at 1450℃ for 5h, and cooled naturally to obtain low-carbon magnesium-carbon refractory for clean steel smelting.

[0047] The mass ratio of andalusite to mullite in the composite additive is 1:3.

[0048] After inspection and testing, the properties of the low-carbon magnesium-carbon refractory material for clean steel smelting prepared in this embodiment are as follows: the room temperature compressive strength is 60MPa, the high temperature flexural strength is 16MPa (1400℃ insulation for 30min); the thermal shock stability can reach 53 times without cracking (1100℃ insulation for 30min, air cooling method); the oxidation index is 21% (1500℃ oxidation for 3h); the erosion index is 35% (1500℃ erosion for 3h). Example 6

[0049] In this embodiment, low-carbon magnesium-carbon refractory materials for clean steel smelting are prepared according to the following method: 41wt% 3-5mm fused magnesia, 25wt% 1-3mm fused magnesia, 18wt% ≤74μm fused magnesia, 11wt% silicon powder, 1wt% alumina powder, 4wt% flake graphite are used as raw materials, and 2wt% composite additives (andalusite, mullite) and 6wt% phenolic resin are added. First, magnesia fine powder, silicon powder, alumina powder, flake graphite and composite additives are mixed to obtain composite powder; then magnesia aggregate is mixed with phenolic resin, and then the above composite powder is added, and the secondary mixing is uniform; it is pressed and formed under 170MPa and cured at 110℃ for 16h; then the pressed body is buried in coke, kept at 1500℃ for 3h, and cooled naturally to obtain low-carbon magnesium-carbon refractory for clean steel smelting.

[0050] The mass ratio of andalusite to mullite in the composite additive is 1:2.

[0051] After inspection and testing, the properties of the low-carbon magnesium-carbon refractory material for clean steel smelting prepared in this embodiment are as follows: the room temperature compressive strength is 57MPa, the high temperature flexural strength is 13MPa (1400℃ insulation for 30min); the thermal shock stability can reach 58 times without cracking (1100℃ insulation for 30min, air cooling method); the oxidation index is 23% (1500℃ oxidation for 3h); the erosion index is 37% (1500℃ erosion for 3h).

[0052] Compared with the prior art, the present invention has the following characteristics: The preparation method adopted by the present invention is to mix fused magnesia sand, silicon powder, alumina powder, composite additives, flake graphite and phenolic resin of different particle sizes uniformly, press and shape, solidify, and perform carbon embedding heat treatment to obtain low-carbon magnesium-carbon refractory material for clean steel smelting. The whole process is very simple and suitable for large-scale production. The raw materials used in the present invention can be purchased from the market at a low price and the production cost is low.

[0053] The aluminum oxide and silicon powder used in the present invention generate magnesium aluminum spinel, silicon carbide and forsterite in situ at high temperature. Silicon carbide has a strong affinity for oxygen, slows down the oxidation of graphite, improves the anti-oxidation performance of the material, and silicon carbide reacts with carbon monoxide gas to generate carbon, which can make up for the loss of carbon source; magnesium aluminum spinel and forsterite can absorb and solid-dissolve elements such as magnesium, aluminum and iron in the slag to generate spinel and high-temperature solid solution, and improve the anti-corrosion performance of the material.

[0054] The andalusite used in the present invention will decompose at high temperature to generate columnar mullite and a small amount of silicon dioxide low melting phase (see Figure 1 ), which produces micro-volume expansion to block pores, hinder the entry of oxygen and the penetration of slag, and improve the material's antioxidant and erosion resistance; the low-melting phase of silicon dioxide is excluded from the andalusite and enters the cracks and pores, and is then reconstructed by high temperature into high-melting point silicon carbide and forsterite phases, establishing a strong chemical bond between the aggregate and the matrix, and improving the bonding strength between the matrices, thereby significantly improving the mechanical properties and thermomechanical properties of the refractory material.

[0055] The present invention makes use of the volume expansion effect and intercrystalline phase strengthening effect of in-situ multiphase ceramic phases (such as silicon carbide, forsterite, magnesia-alumina spinel and mullite) to make the prepared low-carbon magnesium-carbon refractory material have excellent oxidation resistance, thermal shock resistance and slag resistance.

[0056] The present invention adopts andalusite powder and mullite powder with micron size, utilizes the size effect to improve the porosity of the material, and at the same time, the excellent thermal shock stability and oxidation resistance of mullite improve the high temperature service performance of the magnesium-carbon refractory material.

[0057] The graphite used in the present invention has a low content, which reduces the risk of carbon addition in molten steel. The prepared magnesium-carbon refractory material has excellent thermal shock resistance, oxidation resistance and corrosion resistance, and is suitable for clean steel smelting.

[0058] After testing, the low-carbon magnesium-carbon refractory material for clean steel smelting prepared by the present invention has excellent service performance: the room temperature compressive strength is 52-63MPa, the high temperature flexural strength is 11-16MPa (1400℃ insulation for 30min); the thermal shock stability can reach 45-60 times without cracking (1100℃ insulation for 30min, air cooling method); the oxidation index is 17-23% (1500℃ oxidation for 3h); the erosion index is 35-41% (1500℃ erosion for 3h).

[0059] In summary, the present invention has the characteristics of low cost and simple process; the low-carbon magnesium-carbon refractory material for clean steel smelting prepared by the present invention has excellent mechanical properties, thermal shock resistance, oxidation resistance and corrosion resistance.

[0060] The above embodiments are preferred implementation schemes of the present invention. In addition, the present invention may also be implemented in other ways. Any obvious replacement without departing from the concept of the present technical solution is within the protection scope of the present invention.

[0061] Finally, it should be emphasized that in order to allow ordinary technicians in the field to more easily understand the improvements of the present invention over the prior art, some descriptions of the present invention have been simplified, and for the sake of clarity, some other elements are omitted in this application document. Those skilled in the art should realize that these omitted elements may also constitute the content of the present invention.

Claims

1. A low-carbon magnesium-carbon refractory material for clean steel smelting, characterized in that: The invention comprises the following components: 40-50wt% of fused magnesia with a particle size of 3-5mm, 20-30wt% of fused magnesia with a particle size of 1-3mm, 10-20wt% of fused magnesia with a particle size of ≤74μm, 8-12wt% of silicon powder, 1-3wt% of alumina powder, 3-5wt% of flake graphite; 2-4wt% of composite additives and 4-6wt% of phenolic resin are added; the composite additives comprise the following components: andalusite and mullite.

2. The low-carbon magnesium-carbon refractory material for clean steel smelting according to claim 1 is characterized in that: The mass ratio of andalusite to mullite is 1:(1-3).

3. The low-carbon magnesium-carbon refractory material for clean steel smelting according to claim 1 is characterized in that: The particle size of the andalusite is ≤38 μm, and the purity is ≥80 wt %; the particle size of the mullite is ≤44 μm, and the purity is ≥96 wt %.

4. The low-carbon magnesium-carbon refractory material for clean steel smelting according to claim 1 is characterized in that: The purity of the fused magnesia is ≥98wt%.

5. The low-carbon magnesium-carbon refractory material for clean steel smelting according to claim 1 is characterized in that: The silicon powder has a particle size of ≤74 μm and a purity of ≥99 wt %.

6. The low-carbon magnesium-carbon refractory material for clean steel smelting according to claim 1, characterized in that: The alumina powder has a particle size of 5 to 6 μm and a purity of ≥ 99 wt %.

7. The low-carbon magnesium-carbon refractory material for clean steel smelting according to claim 1 is characterized by: The flake graphite has a particle size of ≤150 μm and a purity of ≥98 wt %.

8. The low-carbon magnesium-carbon refractory material for clean steel smelting according to claim 1 is characterized by: The phenolic resin is a thermosetting phenolic resin, and the solid content is ≥73wt%.

9. The method for preparing the low-carbon magnesium-carbon refractory material for clean steel smelting according to any one of claims 1 to 8, characterized in that: The following steps are involved: Firstly, magnesia fine powder, silicon powder, alumina powder, flake graphite and composite additives are mixed to obtain composite powder; then magnesia aggregate is mixed with phenolic resin, and then the composite powder is added to perform secondary mixing evenly; and low-carbon magnesia-carbon refractory materials for clean steel smelting are prepared by pressing, curing and carbon embedding heat treatment.

10. The method for preparing a low-carbon magnesium-carbon refractory material for clean steel smelting according to claim 9, characterized in that: The pressure of the pressing molding is 150-200 MPa, the temperature of the curing is 90-120° C., the time is 12-18 hours, and the temperature of the heat treatment is 1400-1500° C., the time is 3-5 hours.

Citation Information

Patent Citations

  • Refractory castable for desulfurizing spray gun for pretreating molten iron

    CN101844933A

  • Wear-resistant castable for waste incinerators

    CN105924188A

  • Low-thermal-conductivity thermal-shock-resistant wear-resistant brick and production process thereof

    CN111646807A

  • In-situ multiphase ceramic network combined low-carbon magnesia-carbon refractory material and preparation method thereof

    CN117326852A

  • KR20200057293A

Cited By

  • Preparation method of multi-ceramic combined lightweight magnesia-carbon composite material

    CN120398517A

  • Magnesia-carbon refractory material with high thermal shock resistance and erosion resistance and preparation method thereof

    CN120794578A

  • Tundish dry material suitable for ultra-low carbon steel smelting and preparation method thereof

    CN121627422A

  • Low-carbon magnesia-carbon refractory material with high thermal shock resistance and slag corrosion resistance and preparation method of low-carbon magnesia-carbon refractory material

    CN122010534A